A review of the impact of shift-work on cancer: summary of the evidence for practitioners. Issue 1 (2nd January 2018) - Cherrie, John William; Crawford, Joanne O.; Davis, Alice; Dixon, Ken; Alexander, Carla; Cowie, Hilary; McElvenny, Damien Martin
Abstract: Shift work that involves disruption to the body's circadian rhythm is classified as probably carcinogenic to humans based on limited evidence in humans and sufficient evidence in experimental animals. This article draws together the available information from the epidemiological, mechanistic and health and safety practice research to provide advice for practitioners. There is evidence that the increase in breast cancer risk amongst women who have worked night shifts is relatively modest and we cannot exclude the possibility that there is no cancer risk. If a causal association exists, the most likely mechanism is night time suppression of the production of the hormone melatonin. However, the observed increased risk of breast cancer amongst night shift workers may be due to higher prevalence of obesity and other lifestyle risks in this group of women. Current health and safety policies for shift work generally do not address cancer risks. Employers should develop a workplace policy for night work that informs workers about the potential cancer risks and possible strategies to minimize risks. Employers should also help reduce the cancer risk for shift workers through health promotion initiatives and encouraging access to cancer screening programmes. We summarize the evidence and recommendations in an infographic.